Current and future applications of corneal cross-linking. Issue 3 (May 2015) - Khandelwal, Sumitra S.; Randleman, J. Bradley
<x xml:space="preserve">Abstract</x> Purpose of review To review current concepts and future directions of corneal cross-linking (CXL) as a treatment for keratoconus, ectasia after refractive surgery and infectious keratitis. Recent findings Several important laboratory and clinical studies have established the safety and success of corneal cross-linking for the treatment of keratoconus and other corneal ectasias. Recently, additional studies have analyzed new directions and controversies in corneal cross-linking, exploring new indications, comparing new techniques and analyzing results of new protocols. Summary The results of bench and clinical research are providing the foundation to allow for protocol modifications of the standard cross-linking protocols and expansion of cross-linking concepts for techniques such as accelerated cross-linking, epithelium-sparing protocols and measurement of progression and success.